Vpliv medpoklicnega izobraževanja medicinskih sester na njihovo medpoklicno sodelovanje - Kamenšek, Tina (Obzornik zdravstvene nege, 2020)
Introduction: Patient care is a complex process and requires an effective co-operation of various of health and social care professions. Inter-professional education can be a successful way of improving inter-professional collaboration and patient care. The purpose of the literature review was to examine the impact of interprofessional education of nurses on their inter-professional collaboration with other health care professions and identify any measuring instruments for studying this impact. Methods: Scientific articles published in the bibliographic bases CINAHL, MEDLINE and PubMed Central between 2011 and 2018 were analyzed using a systematic literature review. Articles that were analyzed dealt with employed nurses and nursing students who were inter-professionally educated and who cooperated with other health and social care professions. Results: From the 1,277 identified publications, nine sources were included in the final analysis. Seven studies reported that inter-professional collaboration was better after completing inter-professional education. There was increased mutual respect among the participants, better interpersonal self-confidence and improved positive opinion about the role of health care providers who were also involved in care for patients. However, two studies reported that inter-professional collaboration did not have an impact on the above-written factors. Various measuring instruments for assessing the effectiveness of inter-professional education on interprofessional collaboration were identified. Discussion and conclusion: The results confirm the importance of introducing inter-professional education into the compulsory part of nursing care study programs. In the future, a larger longitudinal study should be conducted that would study the inter-professional education of nurses and confirm its impact on their interprofessional collaboration in practice.
Keywords: collaboration; healthcare; learning; nursing; sodelovanje; učenje; zdravstvena nega; zdravstveni tim